Stereotip Perempuan dalam Bahasa Indonesia dalam Ranah Rumah Tangga - Suyanto AW; Sri Puji Astuti (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2013)
Women stereotype reflected in Indonesian language shows male superiority power upon female insociety that belong to patriarchy ideology. In this kind of society female is always in a possition ofsubordination which are determined by among others, history, culture, and social factors. Womenstereotype as reflected in Indonesian language were found up via vocabularies, idiom, terminology, andtaboo words. This stereotype were connected with social factors, (age, sex, education, andemployment), culture, history, as sources of explanation. Female stereotype in Indonesian language arefound in words, verbal abuse, and verbal taboos. Productive words that stereotype female in Indonesianlanguage are verb, noun, and adjective. The verbs are classified into the once used by adult and theothers used by children. So do the noun. While the adjective tend to be connected with characters,physical, and women’s skill. Among three categories word mentioned above, nouns are the mostproductive to mark female stereotype in Indonesian language. While idioms are found more tostereotype female than male. Some examples for female are: jago masak, ayam kampus, daun muda,kupu malam, ciblek, and so on. Some exemples concerning with male are: mata keranjang, jago makan,mulut besar, and so on. Taboos and abuse words were found only used by male. These kind of wordsmostly concern with human vital organ and sexuality. Social factors that influence the stereotype offemale in Indonesian are sex, education, and employment. In this case, education leaves the other twobehind significantly. The more education reason are the more aware of gender sensitive that personlevel of education have negative correlation with perception on women stereotype. Others factors whichalso have strong influence upon women stereotype in Indonesian language are culture, and morespecific is religion.